Smart departmental store - Islam, Nabirul; Rizwan, Kazi Tanjib; Nifa, Shamima Islam (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2013.